Anti-arrhythmic action of total flavones of Choerospondias axillaris fructus - LI Zeng-xi; TIAN Feng-ju; WU Xiu-ying; ZHANG Yu-ping; TIAN Li; SHI Shan (Acta Pharmacologica Sinica, 2016)
Total flavones (TF) were isolated from the fructus of Choerospondias axillaris (Roxb). Burtt et Hill. TF 5.6mg/kg iv counteracted the atrial fibrillation (flutter) induced by iv CaCl2-Ach in mice. The atrial fibrillation (flutter) occurred in 9/11 mice in control group, while only 5/13 mice in TF group. The onset of arrhythmia induced by iv Ac 20 μg/kg in anesthetized rats was markedly retarded by iv TF 11.2 mg/kg. The onset of VP, VT,VF and HS was delayed 253, 104, 126 and 71% resoectively in comparison with the control group. TF 11.2mg/kg iv elevated the doses of iv Oua 10μg/min to induce VP, VT, VF and HS in anesthetized guinea pigs for 30, 41, 20 and 35% respectively. The adrenalin-induced arrhythmia in conscious rabbits was reduced by iv TF 11.2mg/kg, the onset of the arrhythmia was markedly delayed from 0.2±0.1 to 0.5±0.2 min and the duration of the arrhythmia was markedly shortened from 7±5 to 2.3±1.5 min. The arrhythmia induced by iv BaCl2 13 mg/kg in rats was immediately recovered to a normal sinus rhythm by iv TF 11.2 mg/kg. LD50:iv TF 112±12 mg/kg, iv diphenylhydantoin 39±3 mg/kg, iv propranolo 1.9±0.2 mg/kg, iv lidocaine 117±10 mg/kg. The action of iv TF 11.2 mg/kg against the arrhythmia induced by iv Ac was more remarkable than that of iv DPH 3.9 mg/kg, and that against the arrhythmia induced by iv Oua was similar to that of iv DPH3.9 mg/kg. However, iv Lid was ineffective. The effect of iv TF 11.2 mg/kg on arrhythmia induced by Adr was similar to that of iv Pro 0.2 mg/kg but better than that of Lid.